PERANAN DEPRIVASI TIDUR TERHADAP PEREKAMAN EEG PADA PASIEN TERSANGKA EPILEPSI - Radya Nurhamida Thayeb*, Nizar Yamanie**, Fitri Octaviana*, Joedo Prihartono** (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION EEG IS AN ESSENTIAL INVESTIGATIVE TOOL FOR USE IN PEOPLE WITH EPILEPSY AND UP UNTIL NOW STILL REMAINS CENTRAL IN THE DIAGNOSIS AND CLASSIFICATION OF EPILEPSIES THE YIELD OF INTERICTAL EPILEPTIFORM DISCHARGES IEDS CAN BE INCREASED BY MANY ACTIVATION METHODS AMONG THEM IS SLEEP DEPRIVATION